Surgical outcome following laminectomy and posterior instrumentation for multi-level cervical degenerative disc disease (Nepal Journal of Neuroscience, 2026)
Introduction: Multilevel cervical degenerative disc disease is a major cause of spinal cord compression leading to progressive myelopathy. Posterior decompression with instrumentation provides effective decompression with spinal stability.Methods: A prospective observational study was conducted among 34 patients undergoing multilevel cervical laminectomy with posterior instrumentation. Clinical outcomes were assessed using mJOA score, Visual Analog Scale (VAS), and Nurick grading. Neurological recovery was evaluated using the Hirabayashi recovery rate. Cervical lordosis was measured using the C2–C7 Cobb angle.Results: The mean age was 58.1±8.2 years. Significant improvement was observed in mJOA, VAS, and Nurick grade (p